Exploring mitochondrial biomarkers for Friedreich's ataxia: a multifaceted approach - Stovickova, Lucie; Hansikova, Hana; Hanzalova, Jitka; Musova, Zuzana; Semjonov, Valerij; Stovicek, Pavel; Hadzic, Haris; Novotna, Ludmila; Simcik, Martin; Strnad, Pavel; Serbina, Anastaziia; Karamazovova, Simona; et al. (Journal of neurology, 2024)
This study presents an in-depth analysis of mitochondrial enzyme activities in Friedreich's ataxia (FA) patients, focusing on the Electron Transport Chain complexes I, II, and IV, the Krebs Cycle enzyme Citrate Synthase, and Coenzyme Q10 levels. It examines a cohort of 34 FA patients, comparing their mitochondrial enzyme activities and clinical parameters, including disease duration and cardiac markers, with those of 17 healthy controls. The findings reveal marked reductions in complexes II and, specifically, IV, highlighting mitochondrial impairment in FA. Additionally, elevated Neurofilament Light Chain levels and cardiomarkers were observed in FA patients. This research enhances our understanding of FA pathophysiology and suggests potential biomarkers for monitoring disease progression. The study underscores the need for further clinical trials to validate these findings, emphasizing the critical role of mitochondrial dysfunction in FA assessment and treatment.
Keywords: Young Adult; Ubiquinone (Coenzyme Q10); Mitochondrial dysfunction; Mitochondria; Male; kohortové studie; biologické markery; citrátsynthasa; Biomarkers; mladý dospělý; Cohort Studies; ubichinon; Adolescent; Complex IV (COX); Friedreich's ataxia; Adult; dospělí; mužské pohlaví; Therapeutic monitoring; Neurofilament light chain (NFL); Citrate (si)-Synthase; Disease monitoring; mladiství; lidé; Complex I (NQR); ženské pohlaví; Humans; Ubiquinone; Friedreich Ataxia; Friedreichova ataxie; Female; lidé středního věku; Complex II (SQR); mitochondrie; Middle Aged